Comparative study of essential oil composition of the aerial parts of three populations of Acorus calamus in Iran - A Gholipour; A Sonboli; M Golshahi (Institue of Medicinal Plants, ACECR, 2015)
Background: Multiple medicinal properties of Acorus calamus, a recently rediscovered plant species in Iran were reported. It is not available any information about chemical composition of essential oil of the species in Iran, therefore such study is necessary. Objective: In this research essential oil composition of aerial parts of three populations of Acorus calamus was studied. Methods: Plant materials were collected from their natural habitats in Mazandaran Province (Arzefoon, Pelesk and Alandan). Essential oils were obtained by hydrodistillation and analyzed using GC and GC-MS. Results: In total, 41 components were characterized, and are reported for the first time from Iran. The essential oil yield is 0.5 %, 0.45% and 0.48 % in Arzefoon, Pelesk and Alandan populations respectively. The main compounds identified in the oils are cis-asarone (27-53 %), calamusenone (6.6-9.8 %), (E)-caryopyllene (6.3 - 7.3 %), trans-asarone (4.7 - 6.6 %), acorenone (3.6 - 4.9 %) and (E)-β-farnesene (0.8 - 5 %). Conclusion: The results revealed that essential oil compositions of three studied populations are quantitative and qualitatively different from each other and also other samples from various origins which could be attributed to their ecological growing factors such as altitude.